VALUES OF ISLAMIC EDUCATION IN LOCAL WISDOM OF THE BAJO TRIBE - Bulhayat; Baharun, Segaf; Jaudi, Jaudi; Suwandi, Suwandi (Jurnal Pendidikan Islam, 2023)
This study aims to capture the values of Islamic education in the local wisdom of the Bajo people in the Mandar Archipelago Village along Sumenep, Madura. The values of Islamic education can be seen in the local wisdom of the Bajo people, such as in the ritual before going to sea called Nyalamak and Pongkak Mamie. This study uses a realist ethnographic approach. The source of data through observation and in-depth interviews. The results of this study indicate that there are three aspects of Islamic educational values contained in the local wisdom of the Bajo people: 1) Aqidah values, seen in the strength of belief in going to sea, 2) Worship values, seen from the ritual of reading the book al-Barzanji before going to sea, this is done as a form of gratitude to Allah SWT, 3) Moral values, seen from the way the Bajo people help each other and share among fellow Bajo people. From this series of rituals, it can teach that humans as servants of Allah should always approach and ask only Allah SWT, besides that humans as social beings cannot be separated from the process of interaction both with fellow humans and with the natural surroundings. In this interaction process which means it also contains the values of Islamic education and that is the true essence of Islamic education.